2021
DOI: 10.31234/osf.io/7k9gx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of political devotion in sharing partisan misinformation and resistance to fact-checking

Abstract: Online misinformation poses a significant threat to global challenges such as pandemics and climate change. To understand what drives individuals to share misinformation, we conducted two pre-registered experiments with conservatives and far-right supporters in the US and Spain (N = 1,609) and a neuroimaging study with far-right supporters in Spain (N = 36). Individuals who felt their personal identity was fused with their political group were more likely to share misinformation, especially around sacred moral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…A third theoretical perspective rooted in political psychology implicates ideology in susceptibility to falsehoods (31)(32)(33)(34)(35). We find consistent associations with participants' responses to two items from the World Values Survey regarding government policies: Valuing democracy was associated with higher truth discernment in all countries (meta-analytic b=0.045, z=8.80, p<0.001); and fiscal conservatismas measured by the endorsement of individual responsibility over government supportwas associated with worse truth discernment in most countries (meta-analytic b=-0.015, z=4.63, p<0.001).…”
Section: Who Falls For Misinformation?mentioning
confidence: 99%
“…A third theoretical perspective rooted in political psychology implicates ideology in susceptibility to falsehoods (31)(32)(33)(34)(35). We find consistent associations with participants' responses to two items from the World Values Survey regarding government policies: Valuing democracy was associated with higher truth discernment in all countries (meta-analytic b=0.045, z=8.80, p<0.001); and fiscal conservatismas measured by the endorsement of individual responsibility over government supportwas associated with worse truth discernment in most countries (meta-analytic b=-0.015, z=4.63, p<0.001).…”
Section: Who Falls For Misinformation?mentioning
confidence: 99%
“…However, recent studies and a meta-analysis suggest that the effect of accuracy nudges may be relatively weak (9), especially among conservatives, Republicans, and far-right supporters (10,11). This is in line with the Identity-Based Model of Political Belief (12), which posits that individuals are more likely to believe and share misinformation when their partisan motives outweigh accuracy concerns (13).…”
Section: Introductionmentioning
confidence: 60%
“…Extreme partisanship. Interventions to counter misinformation are often less effective when partisan incentives outweigh accuracy concerns, for instance, when misinformation is framed in terms of group-relevant sacred values, and for individuals who highly identify with the group (11). Thus, we tested if the Misleading count was also less effective in these conditions.…”
Section: Political Affiliationmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Second, accuracy primes can be moderated by partisanship such that they appear to be ineffective for people who strongly identify as conservative, at least in the United States. [38][39][40] Third, there is some indication that the effect conferred by accuracy primes occurs predominantly in the first few seconds after exposure (the treatment effect dissipated after participants rated about 7 headlines), although this initial finding requires further investigation. 39 Finally, a recent study into the performance of "nudge" interventions (which accuracy primes/nudges fall under) in controlled laboratory experiments compared to "in the wild", found that the take-up effect of such interventions in the lab is about 6.2 times larger than in the field (8.7% vs 1.4% 41 ).…”
Section: Accuracy Primes: Priming People To Be Mindful Of Accuracymentioning
confidence: 99%